NUTRITIONAL CHARACTERISTICS OF THE TWO FERMENTED FISH PRODUCTS - HENTAK AND NGARI OF MANIPUR. - SAROJNALINI, CH.; VISHWANATH, W. (Journal of Indian Fisheries Association, 2015)
Proximate composition and nutritional characteristics of the twofermented fish products Hentak and Ngari of Manipur (India) wereevaluated. Percentage of moisture, protein, lipid and ash contents inHentak and Ngari were respectively, 36.30 versus 36.03; 33.33 versus 38.38;13.60 versus 13.34 and 11.43 versus 5.49. Digestibility values in feedingtrials in laboratory rats for 28 days were 82.37% for Hentak 89.46% forNgari and that of Casein was 92.69%. The biological value, food conversionratio and protein efficiency ratio (PER) of Hentak were 96.94, 4.83 and1.8 respectively and that of Ngari were 97.83, 3.17 and 1.8 respectively.The a amino nitrogen of Hentak and Ngari in Pepsin + Trypsin phasewere 28.40 and 28.92 respectively. The TBA number, peroxide value andTVBN were within the acceptable limits.